2021
DOI: 10.1249/mss.0000000000002745
|View full text |Cite
|
Sign up to set email alerts
|

Energy Expenditure of a Male and Female Tennis Player during Association of Tennis Professionals/Women’s Tennis Association and Grand Slam Events Measured by Doubly Labeled Water

Abstract: The version presented here may differ from the published version or from the version of the record. Please see the repository URL above for details on accessing the published version and note that access may require a subscription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…No previous studies have assessed the TDEE using the DLW approach in a representative group of Paralympic athletes. Our data revealed an average TDEE of approximately 2900 kcal•d −1 , which aligns with a recent case study of a wheelchair tennis player, where the TDEE measured by DLW was reported to be between 3118 and 3368 kcal•d −1 (24). These TDEE data of Paralympic athletes are considerably higher than estimates of the energy requirements derived from analyzing the energy intake of weight-stable athletes with SCI (16) and wheelchair athletes (14), with energy intakes ranging from 1500 to 2300 kcal•d −1 .…”
Section: Discussionsupporting
confidence: 91%
“…No previous studies have assessed the TDEE using the DLW approach in a representative group of Paralympic athletes. Our data revealed an average TDEE of approximately 2900 kcal•d −1 , which aligns with a recent case study of a wheelchair tennis player, where the TDEE measured by DLW was reported to be between 3118 and 3368 kcal•d −1 (24). These TDEE data of Paralympic athletes are considerably higher than estimates of the energy requirements derived from analyzing the energy intake of weight-stable athletes with SCI (16) and wheelchair athletes (14), with energy intakes ranging from 1500 to 2300 kcal•d −1 .…”
Section: Discussionsupporting
confidence: 91%
“…When compared to our previous data from a male AB player, we report lower absolute TEE during training (3177 vs 3712 kcal•day −1 ) and competition (3368 vs 5520 kcal•day −1 ). 21 To the best of our knowledge, currently no DLW data exists that has explored the TEE of full-time paralympic athletes to compare. To contextualise the data shown here, TEE during P3 is comparable to that of AB English Premier League soccer players (3566 ± 585 kcal•day −1 ).…”
Section: Discussionmentioning
confidence: 99%
“…In practice, DLW is often used to assess energy expenditure, in order to inform on optimal energy intake in various situations (11,(21)(22)(23)(24)(25)(26)(27). Energy expenditure is calculated from CO 2 production using an (estimated) respiratory quotient or measured food quotient (4,10).…”
Section: Discussionmentioning
confidence: 99%